You are on page 1of 9

Session - 10

Logical equivalence & implications of quantified statements:


Let p(x) & Q(x) be open statement defined for a given universe..
Logical equivalence
The two statement p(x) & Q(x) are said to be logically equivalent
then p(a) Q(a) is true for each replacement a from the universe.
Then we write
( x) ( P(x) Q(x))
Logical Implication
If the implication p(a) -> Q(a) is true for each a in the universe
then we write ( x) ( P(x) => Q(x)) and we say that p(x) logically implies
Q(x).
Converse , Inverse and Contrapositive of a statement of the form ,
( x) ( P(x)-> q(x))
The converse of ( x) ( p(x) -> q(x)) is ( x) ( p(x) -> q(x)).
Inverse : ( x) ( p(x) -> q(x))
Contrapositive: ( x) ( q(x) -> p(x))
Important Equivalences:
The statements ( x) ( P(x)-> Q(x)) and its contrapositive ( x)
( p(x) -> q(x)) are logically equivalent.
i.e ( x) ( P(x)-> Q(x)) <==> ( x) ( Q(x) -> P(x))
further, converse & inverse statements are logically equivalent.
i.e ( x) (Q(x)->p(x)) <= = > ( x) ) ( P(x) -> Q(x)).

Problems:
1.

Prove that ( x) (p(x) q(x) => ( x) p(x) ( x) q(x)

Proof:
Assume that ( x) (p(x) q(x)) is true.
There is atleast one element c in the universe for which p(c)
q (c) is true.
But , p(c) q(c) => p(c)
From the truthe of p (c) we have the true statement ( x) (p(x) an another
true statement similarly, we obtain true statement ( x) (q(x).
( x) (p(x) ( x) q(x)) is also true statement.
Hence ( x) (p(x) ( x) q(x)) is true wherever ( x) (p(x) q(x)) is true, it
follows that
( x) (p(x) q(x)) => ( x) (p(x) ( x) q(x) .
Note:
In a similar way, we can show that , ( x) (p(x) q(x)) => ( x)
(p(x) ( x) q(x)) is a valid statement & so we have,
( x) (p(x) q(x)) =>( x) (p(x) ( x) q(x)).
2) Prove that
a)
[ ( x) p(x) v ( x) q(x)] -> [ p(x)vq(x)] is logically valid.
b)
Also show by counter examples
( x) [p(x) v q(x)] -> ( x) p(x) v ( x) q(x) is not valid.
Proof:
Suppose that, ( x) p(x) v ( x) q(x) is true.
one of the statements ( x) p(x) & ( x) q(x) must be true.
If ( x) p(x) is true , then for every element a in the universe p(a) is true
& hence p(a) v q(a) is true.
a)

Similarly when ( x) q(x) is true,p(a) v q(a) is true for every


element a in the universe.
In both the cases, p(a) v a(a) true for all elements a in the
universe.
[( x) p(x) v q(x)] is true and hence,

[( x) p(x) v ( x)q(x)] -> ( x) [p(x)vq(x)] is valid.

b)
Now consider,
( x) [p(x)vq(x)] , where p(x) : s is even integer & q(x): x is a prime integer
& the universe of discause {2,4,6,3,7}.
For this universe, the statement
( x) [p(x)vq(x)] is true.
But both ( x) p(x) &( x) q(x) are not true .
To show ( x) [p(x)vq(x)] is true while
( x) p(x) V ( x) q(x) is not true.
( x) [ p(x) v q(x)] -> [( x) p(x) v ( x) q(x)]
Is not a valid statement.
3.show that
equivalent.

x p(x) x Q(x) and x (p(x)

Soln:
To show those are not logically equivalent,
Let p(x) : x is positive &
Q(x) : x is negative
With universe of discause: The set of integers.
Then x p(x) x Q(x) is true but
x ( p(x) Q(x)) is false.

Q(x)) are not logically

4.Prove that [( x) p(x) v ( x) q(x)] => ( x) [p(x) v q(x)]


Soln:
Assume that x p(x) v x q(x) is true.
Case (i)
x p(x) is true & xq(x) is true.

For every a , p(a) v Q(a) is true.


( x) [ p(x) v q(x)] is true.

Case (ii)
x p(x) is true &

x q(x) is false for every a in the universe of p(a)

is true & q(a) is false & therefore p(a) v q(a) is true.


( x) [ p(x)

v q(x)] is true.

Case (iii)
x p(x) is false & xq(x) is true

For every a in the universe of p(a) is false & q(a) is true & therefore
p(a)vq(a) is true.
x

[ p(x) v q(x)] is true.

Hence the truth of x p(x) v x q(x) is true statement implies that x


[p(x) v q(x)] is true statement.
x p(x)

v x q(x) => x [p(x)vq(x)]

5.Give an example to show that x[A(x) B(x)] need not be a conclusion


form ( x) A( x) and ( x) B(x).
Soln:
Let A(x): x A, B(x):xB

Let A= {1} & B={2}


Since A & B are non-empty ( x) A( x) & ( x) B(x) are both true.
But ( x)[ A( x) B(x)] is false since AB =
... ( x)[ A( x) B(x)] need not be a conclusion from ( x) A( x) &( x)
B(x).
Equivalences
1. (x) [A(x) v B(x) ] (x) A(x) v (x) B(x)
2. (x) [A(x) B(x)] (x) A(x) (x) B(x)
3. (x) A(x) (x) A(x)
4. (x) A(x) (x) A(x)
5. (x) [A v B(x) ] A v (x) B (x)
6. (x) [A B (x) ] A (x) B(x)
7. (x) A(x) B (x) (A(x) B)
8. (x) A(x) B (x) (A(x) B)
9. A (x) B(x) (x) (A B(x))
10. A (x) B(x) (x) (A B(x))

Implications
1. (x) A(x) v (x) B(x) (x) [ A(x) v B(x)]
2. (x) [A(x) B(x)] (x) A(x) (x) B(x)
3. [B-> A(x)] [ B-> (x)A(x)]

Logical equivalences and implications for quantified statement in one


variable.
For any set of open statements in the variable x & for
prescribed universe, we have the following logical implications &
equivalences.

1. 1. (x) [p(x) q(x)] (x) p(x) (x) q(x)


2. ( x) (p(x) v q(x) ) ( x) p(x) v ( x) q(x)
3. ( x) [p(x) q(x)] ( x) p(x) ( x) q(x)
4. ( x) p(x) v ( x) q(x) ( x) [p(x)vq(x)]
5. ( x) [p(x) q(x) r(x)] ( x) [(p(x) q(x)] r(x)]
6. (x) [p(x)->q(x)] (x) ( p(x) v q(x))
7. ( x) ( p(x)) ( x) p(x)
8. ( x) (p(x) Q(x)) ( x) ( p(x) v Q(x)
9. ( x) (p(x) v Q(x)) ( x) ( p(x) Q(x)
10.( x) [p(x)->Q(x)] [( x) p(x) ->( x) Q(x)]

Negation of quantified statement


The following rules are used for negative statements with one
quantities.
1.
2.
3.
4.

(( x) p(x) (x) ( p(x)


(x) p(x)) ( x) ( p(x))

(( x) p(x)) (x) (p(x))


( (x) p(x)) ( x) (p(x))

PROBLEM:
1. Prove that [( x) p(x) -> Q(x) ] ( x) [p(x) Q(x)]
Sol:
[( ) p(x) -> Q(x)] ( x) [p(x) -> Q(x)]

( x) [ p(x) -> Q(x)]


( x) [p(x) -> Q(x)]

Note:
( x) [R(x) S(x)] [ x] [R(x) S(x)]
[ x) [ R(x) S(x)]

2. Negate & simplify each of the following statement


1.
2.
3.
4.

( x) [p(x) Q(x)]
( x) [P(x) Q(x)]
( x) [P(x) -> Q(x)]
( x) [p(x)vQ(x) -> R(x)]

Soln:

1. ( x) [p(x) Q(x)]
Negation of the statement is
( x) [p(x) Q(x)] ( x) [ p(x) v Q(x)]
( x) [ p(x) Q(x)]
2. (( x) [p(x) Q(x)]
( x) [p(x) Q(x)]

( x) ( p(x) Q(x))

( x) [ (p(x) v Q(x))

3. ( x) [ p(x) -> Q(x)]


[( x) [ p(x) -> Q(x)] ]
( x) [(p(x) -> Q(x)]
( x) [ (p(x) v Q(x)]
( x) [(p(x) v Q(x)]
4. ( x) [(p(x) v Q(x) -> R(x)]
( x) [ p(x) v Q(x) R(x)]
( x) [p(x) v Q(x) R (x)]

3. Negate each of the following propositions.


i) ( x) p(x) ( x)q(y)

ii) ( x) p(x) ( x) q(y)

iii) ( x) p(x) v( x)q(y)

iii) ( x) p(x) v( x) q(y)

v) (( x U) (x+6=25)

vi) ( x U) (x<25)

Sol:
[( x)p(x) ( y) q(y)]
<-> [( x) p(x)] v [( y) q(y)]

i)

< ==> [ (x) p(x)] v [( x) q(y)]


[( x) p(x) ( x) q(y)]
< == > [( x) p(x)] v [( x )q(y)]

ii)

< == > [ (x) p(x)] v [ (x) q(y)]


iii)
iv)
v)

( x) p(x) ( y) q(y)
( x) p(x) ( x) q(y)
( x U) (x+6 25)

4. Write the negation for each of the following statements. Determine


whether
the
resulting
statement
is
true
or
flase.
Assume that the universe of discourse is the set of all real
number.
i)
( x) ( m) (x2<m)
ii)
( m) ( ( x) (x2 m)
Sol:
(i)

The ngation of ( x) ( m) (x2<m) is ( x) ( m) (x2 m). The


meaning of ( x) ( m) is that there exist some real number x
such that x2 m for every real number m.The statement is false as

there is some real number x such that (x2 m) for every m is not
possible.
[( m) ( x) (x2<m)] is ( m)( x) (x2 m ).
The meaning of this statement is that for every real number m,
there exists some real number x such (x2 m). The statement is
true as for every m, there exists some greatest real number x
such that (x2 m ).

(ii)

5.

Let the universe of discourse be the set of all real rational


number. Using quantifiers, express the following statement.
(i)
3 is irrational
(ii) Subtraction of any two rational number is rational
Sol:
(i)
(ii)

(x) (x2 3) (or) [(x) (x2 = 3) ]


(x) (y) [(x-y) is rational]